Optimizing surgical strategies for subaxial cervical fracture-dislocation: a facet and disc injury-based approach - Wang, Shiyong; Yao, Rubin; Gong, Xiangdong; Miao, Xin; Chu, Yandong; Yang, Kaishun; Ge, Zhaohui (Frontiers in Surgery, 2025)
ObjectiveTo investigate the influence of facet joint and intervertebral disc injuries on surgical approach selection in subaxial cervical fracture-dislocation.MethodsWe retrospectively analyzed 150 patients with subaxial cervical fracture-dislocations, stratified by surgical approach: anterior (anterior-only or anterior-posterior) and posterior (posterior-only or posterior-anterior). Preoperative computed tomography (CT) and magnetic resonance imaging (MRI) were assessed to identify injury patterns, and radiographic and clinical outcomes were compared before and after surgery.ResultsThe mean patient age was 48.84 ± 11.68 years, and 86.7% completed at least 12 months of follow-up. The anterior group exhibited significantly higher rates of unilateral facet injuries (53.5% vs. 18.4%), perched/separated facets (59.4% vs. 34.7%), F2-type fractures (46.5% vs. 2%), and disc extrusion (40.9% vs. 15.4%). In contrast, the posterior group had more locked facets (55.1% vs. 15.8%) and non-fracture dislocations (79.6% vs. 23.8%). Bilateral injuries were commonly associated with locked or separated facets and absence of fracture. Patients undergoing combined posterior-anterior surgery had greater incidence of bilateral facet involvement and disc protrusion. Spinal alignment significantly improved postoperatively in all groups (P < 0.05), with no statistical difference in alignment correction between approaches. Twenty-four patients showed no neurological recovery, and 20 patients died during the follow-up period. Complication rates were higher in the posterior group (14.3%) compared to the anterior group (2.97%).ConclusionFacet and disc injury patterns strongly affect surgical decision-making. Anterior approaches are preferable for disc extrusion or facet fractures, while posterior surgery is suited for locked facets without fractures. Accurate injury classification via imaging can guide individualized treatment and improve outcomes.